THE DISTINCTION OF THE FIRST-BORN AND THE YOUNGEST CHILDRENâS INDEPENDENCE IN KINDERGARTENAISYIYAH BUSTANUL ATFHAL 86 CIPAYUNG JAKARTA TIMUR - Vinayastri, Amelia; Hani, Umi (Jurnal Konselor, 2015)
this study aims to find differences between self-reliance and independence firstborn youngest child. The method used in this research is to use the comparative method. In this study took the entire population student in kindergarten Aisyiyah Bustanul Athfal 86 Cipayung, the number 88 students. Sampling technique used is Proportional Random Sampling with a purposive sample of 60 students, 30 students firstborn and 30 students youngest child. Data collection techniques using research instrument in the form of objective tests attitude as much as 31 grains that have been tested for validity and relibility. The analysis technique used is the analysis of the differences with the t-test, at significance level α = 0.05. Test requirements analysis used in this study is the chi-square test for normality and homogeneity test. The results showed, on average, the independence of the firstborn = 82,7 and the average the results of the independence of the youngest child = 76,83. From the results of hypothesis testing using obtained by value = 2.42 and = 1.67 at significance level of 5%,. The results indicate that rejected and be accepted. This means it has prove the truth of the hypothesis thus there is a difference between the independence of the eldest son and youngest child in kindergarten Aisyiyah Bustanul Athfal 86 Cipayung, East Jakarta academic year 2015-2016.Keywords :independence , birth order , the eldest , the youngest child , early childhood .